PHARMACOGNOSTIC STANDARDIZATION OF THE LEAF OF MELALEUCA ALTERNIFOLIA (MAIDEN & BETCHE) CHEEL - Shah, Gagan; Baghel, Uttam Singh (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Melaleuca alternifolia (Myrtaceae) is a well-known, commonly used, tall shrub plant in Ayurvedic medicine. Traditionally, it is used for its antimicrobial potential to treat cutaneous infections. No attempts have been made regarding pharmacognostic investigation of the plant till date. So, the present study was aimed to establish standards with the help of different pharmacognostic parameters.Methods: Various pharmacognostic parameters (morphological, microscopic, physicochemical evaluations and preliminary phytochemical screening) were studied along with fluorescent and thin layer chromatographic analysis of the extract. Result: Morphologically Melaleuca alternifolia is a shrub having height of 7 m with layered and papery bark. Leaves have an arranged pattern, petiole is 1 mm in length; linear-acute with dimensions of 10-35 mm x 1 mm. Organoleptic features shows that leaves have characteristic odour and astringent taste. The transverse section of the leaf reveals the existence of epidermal layers, mesophyll tissues, vascular bundles and secretory cavities. The stomata are anomocytic and leaf constants such as stomatal number is 180-200-225, stomatal index is 3.8-4.4-5.9, vein islet number is 18.68 (average), veinlet termination number 20.3 (average) and palisade ratio is 5.5-6.4-6.9. The results of phytochemical screening showed the occurrence of different phytoconstituents (flavonoids, phenolic tannins, phytosterol and terpenoids).Conclusion: The present study evaluated various pharmacognostic parameters which will help in quality control (standardization) of Melaleuca alternifolia leaves in crude form, in herbal formulation and also aid in the preparation of an herbal monograph for the species.